Impacts of volcanic ejecta on surface water Mt. Pinatubo case - Villados, Danilo P. (2000., 2000)
This study was designed to determine the possible effects of volcanic materials on the surface water of Pampanga River following the deposition of sediments particularly during the rainy season. After the June 1991 eruptions of Mt. Pinatubo, tons of volcanic debris had been deposited over a broad area. On the onset of the rainy season, t hese volcanic materials and pyroclastic fall deposits are mobilized, blocking up all available spaces towards low-lying area. Lahar, a mixture of water and volcanic debris from Mt. Pinatubo contains sediments and minerals which may contaminate rivers along the periphery of Mt. Pinatubo and low-lying rivers including the Pampanga River. The Pampanga River is one of the most important rivers in Cental Luzon suppying about 14,716 million cubic meters of water for agricultural, industrial and domestic/municipal use. At present, the surface water of Pampanga River is being used largely for irrigation of various crops.
The conclusions drawn from the evaluation of the surface water characteristics of the Pampanga River are as follows: 1. The surface water of the Lower Pampanga River (LPR) remains a potential source of surface water for various requirements, despite the continuous flows of lahar from Bamban River Basin. Specifically , the soluble salts and total dissolved solids are at low levels. Sodium content is very low, thus, sodium hazard will not be a problem if ever the water is utilized for irrigation purposes. The river water maintains its high levels of calcium and alkalinity, while sulfate and chloride levels have increased from values obtained in 1976-1977. Their levels however, were still within the acceptable limits. Other water quality parameters were unaffected by the flow of volcanic materials. 2. The results of monitoring in July 1997 indicated the rations of total dissolved solids (TDS), electrical conductivities (EC) and sulfate at Arayat Sampling Station at LPR and San Isidro Sampling Station at Upper Pampanga River (UPR) were 1.3, 1.2 and 2.0, respectively. 3. The results of forecasting indicated that EC and chloride values at Arayat Sampling Station at LPR may reach the 1995-1997 levels observed at San Isidro Sampling Station at UPR after the rainy season of year 2000 and the levels of TDS and sulfate beyond 2001. The rates at which TDS and sulfate are decreasing per year are 3.0 and 4.5%, respectively. 4. Variations in water quality maybe attributed to the intensity of of rainfall, volume of sediments being deposited at the source, and water discharge at Arayat Sampling Station at LPR. 5. The surface waters of both the Lower and Upper Pampanga River, in general, remain a good source of water for irrigation of various crops.
Thesis (M.S. Environmental Engineering)-University of the Philippines Diliman